Chapter La presenza del martire Miniato nelle dedicazioni toscane: alcune occorrenze - Gagliardi, Isabella (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The article examines the dedications to San Miniato martyr in the Tuscan area during the Middle Ages. On the basis of the specific literature, while not excluding that other titles may be recovered from specific studies on territories in the future time, it is hypothesized that in the dioceses of Fiesole, Florence and Pistoia the preservation of these titles is linked to the presence of the Vallombrosan monks who, since the origins of their Order, were linked to the memory of the ancient Christian martyr.